University Youth And Political Socialization: A Research On Fırat University And İnönü University Students - Doğan, Adem; Altunbey, Tuba (Fırat University, 2021)
[EN] Political socialization is a process that continues throughout an individual's life. Individuals are affected by different political socialization tools at different levels in this process. In the process of political socialization, especially the youth phase draws attention as a period in which new experiences took place and shared. In this phase, the university education period includes an important part of the life of the individuals, and it expresses the transition from the environment and groups they were in to a new environment.In this study, it is aimed to determine the level of influence of university youth from groups and tools in the process of political socialization, where they gain knowledge and experience about the political system and political values. Within the framework of this purpose, the data obtained by interviewing with 1500 students studying in different departments of Fırat University and İnönü University with the stratified sampling method and face-to-face survey technique were analyzed.According to the findings obtained, it was determined that different tools had an effect on the formation of young people's political views, thoughts and tendencies. In the political socialization of university youth, apart from primary relations such as family and friendship groups, different tools such as political parties, political leaders and mass media have different levels of influence.

Siyasal toplumsallaşma, bireyin hayatı boyunca devam eden bir süreçtir. Bireyler, bu süreçte farklı siyasal toplumsallaşma araçlarından farklı düzeylerde etkilenmektedir. Siyasal toplumsallaşma sürecinde özellikle gençlik evresi yeni deneyimlerin yaşandığı ve paylaşıldığı bir dönem olarak dikkat çekmektedir. Bu evre içerisinde de üniversite eğitimi dönemi bireylerin yaşamının önemli bir kesitini içermekte, daha önce içine bulundukları çevreden, gruplardan yeni bir çevreye geçişi ifade etmektedir. Bu çalışmada üniversite gençliğinin, siyasal sisteme ve siyasal değerlere ilişkin bilgi ve deneyim kazandığı, siyasal toplumsallaşma sürecindeki gruplardan ve araçlardan etkilenim düzeylerinin belirlenmesi amaçlanmaktadır. Bu amaç çerçevesinde Fırat Üniversitesi ve İnönü Üniversitesi’nde farklı bölümlerde eğitim görmekte olan 1500 öğrenci ile tabakalı örneklem yöntemi ve yüz yüze anket tekniği ile görüşülerek elde edilen veriler analiz edilmiştir. Elde edilen bulgulara göre, gençlerin siyasi görüş, düşünce ve eğilimlerinin oluşmasına farklı araçların etkisinin olduğu belirlenmiştir. Üniversite gençliğinin siyasal toplumsallaşmasında aile ve arkadaşlık grupları gibi birincil ilişkilerin yanı sıra, siyasi parti, siyasi lider ve kitle iletişim araçları gibi farklı araçların farklı düzeylerde etkisi bulunmaktadır.
ÜNİVERSİTE GENÇLİĞİ VE SİYASAL TOPLUMSALLAŞMA: FIRAT ÜNİVERSİTESİ VE İNÖNÜ ÜNİVERSİTESİ ÖĞRENCİLERİ ÜZERİNE BİR ARAŞTIRMA